Changes of Th17/Treg cell and related cytokines in pancreatic cancer patients - Wang, Xiaofang (Int J Clin Exp Pathol, 2015)
To explore the mechanism of Th17 cells and Treg cells in the peripheral blood of patients with pancreatic cancer through analyzing the changes of the related genes and cytokines expression. 40 patients were divided into three groups based on clinical staging, and 20 healthy subjects were treated as normal control. Proportion of Th17 cells and Treg cells were detected by flow cytometry. RORα, RORγt, FoxP3, and CTLA-4 expression in peripheral blood mononuclear cells were detected by RT-PCR. IL-10, IL-23, INF-γ, TGF-β, and IL-17 cytokine levels in peripheral blood were determined by enzyme-linked immunosorbent assay (ELISA). The proportion of Th17 cells in peripheral blood of pancreatic cancer patients was lower than that in the normal control, while the proportion of Treg was higher. RORα and RORγt mRNA expression in Th17 cells from pancreatic cancer patients decreased, while FoxP3 and CTLA-4 mRNA expressions in Treg cells increased compared with the normal control. And the correlation analysis revealed that they were significantly correlated with clinical staging. Compared with healthy control, IL-23, IL-17 and INF-γ levels were lower in pancreatic cancer patients, while IL-10 and TGF-β levels were higher. Following the progression of disease, patients in advanced stage exhibited higher level of IL-10 and TGF-β, and lower levels of IL-23 and INF-γ. Pancreatic cancer patients exhibited Th17/Treg balance disorders with higher Treg and lower Th17 cells. They affect cytokine IL-10, IL-23, INF-γ, TGF-β, and IL-17 expression changes mainly through regulating transcription factors such as RORα, RORγt, FoxP3 and CTLA-4, suggesting that Th17/Treg balance disorders plays an important role in the tumorigenesis of pancreatic cancer.